Optimization of Culture Conditions for Production of Î²-Mannanase by Strain Nonomuraea sp. ID06-379 using Submerged Substrate Fermentation - Ratnakomala, Shanti; Yopi, Yopi; Suhartono, Maggy T; Meryandini, Anja; Prasetya, Bambang (ANNALES BOGORIENSES, 2014)
The objective of this study was to investigate the effect of media compositions on the production of Î²-mannanase by Nonomuraea sp.ID06-379. The study was focused on the influence of carbon, nitrogen,phosphorus and detergents on Î²-mannanase synthesis through manipulating media compositions on production medium. The results indicated that for carbon sources, locus bean gum (0.745 Â± 0.036 U/ml) showed maximum mannanase activity. Malt extract was the best nitrogen source for producing Î²-mannanase (1.075 Â± 0.006 U/ml),(NH4)2HPO4 as phosphate source (1.733 Â± 0.026 U/ml) and Tween 80 (1.145 Â± 0.003 U/ml) as surfactants effect on increasing permeability of bacterial cell membrane, enhancing membrane transport and excretion of extracellular enzymes into the production media. The results showed that 1% malt extract, 0.5% locus bean gum and 0.05% (NH4)2HPO4 were good substances for nitrogen source, carbon source and phosphate respectively. The highest production of Î²-mannanase by Nonomuraea sp. ID06-379 (5.33 U/mg) was reached in the medium optimization (Vogelâs minimal medium) contained the following ingredients: 0.5% locus bean gum, 1% malt extract and 0.05% (NH4)2HPO4, under submerged fermentation with shaking at 120 rpm and 28 ï°C for 2 days incubation.